Folkekirkens ejendomsforhold og økonomi - historisk belyst: Danske teologer og blodskam 1680-1770 - Stenbæk, Jørgen (Kirkehistoriske Samlinger, 2003)
The history of property and economics of the established church of Denmark (»Den danske Folkekirke«) reaches back into the pre-reformation era. During the reformation the properties of the bishoprics were confiscated by the king, but the parishes and their properties were left undisturbed. By the time of the constitutional Act of the Kingdom of Denmark (1849), which created the modern established church (»Den danske Folkekirke«), the properties of this church still by law were enumerated in two parts, managed after beneficial principles of civil law, namely the local church (and cemetery) with its property, managed by the church patron, and the benefice of the parish, managed by the vicar. In cities and towns the properties were managed by the council and the local rector after specific (and different) rules. The constitutional discussions in 1849 did not immediately change and clarify the ownership of the church property, and different views were presented during the negotiations. During the following periods of Danish constitutional history and until the present day the Danish parliament step by step has changed this beneficial civil law system of church property into a modem complicated public law system with a combination of government grant, proceeds of church properties and church rates, managed partly by the state (the ministry of ecclesiastical affairs), partly by diocesan authorities and local elected ecclesiastical bodies (parish councils and deanery committees).